Biofilm density and detection of biofilm-producing genes in methicillin-resistant Staphylococcus aureus strains - Szczuka, Ewa; Urbańska, Katarzyna; Pietryka, Marta; Kaznowski, Adam (Folia microbiologica, 2013)
Many serious diseases caused by Staphylococcus aureus appear to be associated with biofilms. Therefore, we investigated the biofilm-forming ability of the methicillin-resistant S. aureus (MRSA) isolates collected from hospitalized patients. As many as 96 % strains had the ability to form biofilm in vitro. The majority of S. aureus strains formed biofilm in ica-dependent mechanism. However, 23 % of MRSA isolates formed biofilm in ica-independent mechanism. Half of these strains carried fnbB genes encoding surface proteins fibronectin-binding protein B involved in intercellular accumulation and biofilm development in S. aureus strains. The biofilm structures were examined via confocal laser scanning microscopy (CLSM) and three-dimensional structures were reconstructed. The images obtained in CLSM revealed that the biofilm created by ica-positive strains was different from biofilm formed by ica-negative strains. The MRSA population showed a large genetic diversity and we did not find a single clone that occurred preferentially in hospital environment. Our results demonstrated the variation in genes encoding adhesins for the host matrix proteins (elastin, laminin, collagen, fibronectin, and fibrinogen) and in the gene involved in biofilm formation (icaA) within the majority of S. aureus clones.
Keywords: Methicillin-Resistant Staphylococcus aureus; Microscopy, Confocal; biofilmy; Biofilms; konfokální mikroskopie; Humans; lidé; methicilin rezistentní Staphylococcus aureus